Estimation of Direct Fire Emissions from Forests Burning in Siberia - Ponomarev (The 3rd International Electronic Conference on Atmospheric Sciences, 2020)
Using a database on wildfires recorded by remote sensing for 1996–2020, we assessed the seasonal variation of direct carbon emissions from the burning in Siberian forests. We have implemented an approach that takes into account the combustion parameters and the changing intensity of the fire (in terms of Fire Radiative Power (FRP)), which affects the accuracy of the emission estimate. For the last two decades, the range of direct carbon emissions from wildfires was 20–250 Тg С per year. Sporadic maxima were fixed in 2003 (>150 Тg С/year), in 2012 (>220 Тg С/year), and in 2019 (>190 Тg С/year). Preliminary estimation of emissions for 2020 (on 30th of September) was ~180 Tg С/year. Fires in the larch forests of the flat-mountainous taiga region (Central Siberia) made the greatest contribution (>50%) to the budget of direct fire emission, affecting the quality of the atmosphere in vast territories during the summer period. According to the temperature rising and forest burning trend in Siberia, the fire emissions of carbon may double (220 Тg С/year) or even increase by an order of magnitude (>2000 Тg С/year) at the end of the 21st century, which was evaluated depending on IPCC scenario.